Analysis of an Antarctic ice core by ion chromatography (Mg2+, Na+, Cl−, and SO42− content) - Marques, Magdalena de Mello; Peralba, Maria do Carmo Ruaro; Simões, Jefferson Cardia; Bernardo, Ronaldo Torma; Sneed, Sharon B.; Casassa, Gino (Geochimica Brasiliensis, 2014)
This study presents the ion chromatography analysis of an Antarctic ice core (IC-3; 85°59’S, 81°35’W) and discusses Mg2+, Na+, Cl-, and SO42− concentration data. The Mg2+, Na+ and Cl- concentration peaks, are environmentally interpreted as winter layers and lower concentrations are considered as summer ones and can be directly associated to sea spray. The higher concentrations in winter are probably caused by transport of marine air masses over the Antarctic ice sheet, which are stronger in this season. There are probably additional sources for Cl− in the IC-3 core region, which could have originated from gaseous HCl adsorption processes, essentially as a result of acid–base reactions between NaCl and HNO3 or H2SO4 in aerosol particles or directly over the snow surface.